PERAMPASAN ASET KORUPTOR MELALUI MEKANISME NON CONVICTION BASED ASSET FORFEITURE SEBAGAI EFEKTIVITAS PENGEMBALIAN KERUGIAN NEGARA BERDASARKAN UNITED NATIONS CONVENTION AGAINST CORRUPTION (UNCAC) 2003 - Ramadhana Ari Pratamas Bangun; Evi Deliana; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Efforts to confiscate corrupt assets tend not to be easy to do, because corruptors often hide assets resulting from their crimes abroad that are difficult to penetrate the country's law. Assets resulting from crime are stored in various forms, one of which is in the form of a bank account. Therefore, there is a solution and a breakthrough contained in Article 54 Paragraph (1) letter c of UNCAC 2003, namely deprivation of assets without punishment which is one of the efforts that can be made to return assets to the state or to parties entitled to ownership of unnatural assets that are not allegedly due to a crime that must not be preceded by criminal charges. This is considered effective in recovering state losses due to corruption. The formulation of the problems in this study are First, How is the relationship of deprivation of corrupt assets through the mechanism of non-conviction based asset forfeiture as the effectiveness of state loss recovery based on the 2003 United Nations Convention Against Corruption (UNCAC) related to human rights? Second, how is the ideal arrangement and implementation of the seizure of corrupt assets through the mechanism of non-conviction based asset forfeiture as the effectiveness of returning state losses in Indonesia?The research method used is the type of normative legal research or library law research. The study was conducted on legal principles and legal comparisons related to the problem under study. This research was obtained by studying and studying books, laws and regulations, various scientific works, and others. Data analysis in this research was carried out qualitatively and quantitatively.The result of this research is that the mechanism of appropriation of assets without criminal punishment does not violate the human rights of a person's right to own assets or assets, while the assets owned come from a legitimate source. However, for assets or assets originating from proceeds of crime and causing state financial losses, the confiscation of these assets must be carried out. This is precisely as a form to restore state finances and restore other human rights that have been violated by the perpetrators of corruption. In relation to human rights, confiscation of assets without punishment does not violate the presumption of innocence and the principle of non-self-incrimination inherent in the perpetrator. Furthermore, it is necessary to immediately adjust or adjust the laws and regulations in Indonesia relating to crime, especially corruption, regarding the mechanism of appropriation of assets without punishment as offered in UNCAC 2003 and has been ratified by the Government of Indonesia with Law Number 7 Year 2006. Then, the Government of Indonesia (both executive and legislative) immediately finishes the discussion of the Draft Law on the Seizure of Asset Without Criminalization.Keywords: Confiscation, Assets, NCB, State Losses, UNCAC.